2017
DOI: 10.1002/anie.201702785
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic‐Macroion‐Induced Formation of Bicontinuous Block Copolymer Nanocomposites with Enhanced Conductivity and Modulus

Abstract: A facile and electrostatically driven approach has been developed to prepare bicontinuous polymer nanocomposites that is based on the polyoxometalate (POM) macroion induced phase transition of PS-b-P2VP from an initial lamellar phase to a stable bicontinuous phase. The multi-charged POMs can electrostatically cross-link P2VP blocks and give rise to bicontinuous phases in which the POM hybrid conductive domains occupy a large volume fraction of more than 50 %. Furthermore, the POMs can give rise to high proton … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
74
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(80 citation statements)
references
References 51 publications
1
74
0
2
Order By: Relevance
“…Additionally the composite exhibits high chemical and thermal stability and increased water retention, useful for proton conduction membranes in fuel cells. In a related study, Li and colleagues showed that POM anions can be used to modulate the structure of cationic block copolymer matrices . While the non‐functionalized block copolymer (PS‐ b ‐P2VP, poly(styrene‐ block ‐2‐vinylpyridine)) forms well‐behaved lamellar structures, POM incorporation leads to the formation of bicontinuous nanocomposite structures with phase separation on the <100 nm scale.…”
Section: Emerging Areas and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally the composite exhibits high chemical and thermal stability and increased water retention, useful for proton conduction membranes in fuel cells. In a related study, Li and colleagues showed that POM anions can be used to modulate the structure of cationic block copolymer matrices . While the non‐functionalized block copolymer (PS‐ b ‐P2VP, poly(styrene‐ block ‐2‐vinylpyridine)) forms well‐behaved lamellar structures, POM incorporation leads to the formation of bicontinuous nanocomposite structures with phase separation on the <100 nm scale.…”
Section: Emerging Areas and Perspectivesmentioning
confidence: 99%
“…In a related study, Li and colleagues showed that POM anions can be used to modulate the structure of cationic block copolymer matrices. [161] While the non-functionalized block copolymer (PS-b-P2VP, poly(styrene-block-2-vinylpyridine)) forms well-behaved lamellar structures, POM incorporation leads to the formation of bicontinuous nanocomposite structures with phase separation on the < 100 nm scale. The authors suggest that the POM ([SiW 12 O 40 ] 4À ) promotes micellar structures within the block Figure 8.…”
Section: Heterogeneous Cationic Matricesmentioning
confidence: 99%
“…Zudem zeigt das Komposit hohe chemische und thermische Stabilität sowie erhöhte Wasserrückhaltekraft, was nützlich für den Einsatz als protonenleitfähige Membran in Brennstoffzellen ist. In einer damit verbundenen Studie zeigten Li und Mitarbeiter, dass POM‐Anionen genutzt werden können, um kationische Block‐Copolymermatrices zu modifizieren . Während das nichtfunktionalisierte Block‐Copolymer Poly(styrol‐ block ‐2‐vinylpyridin (PS‐ b ‐P2VP) geordnete lamellare Strukturen bildet, führt die POM‐Integration zur Bildung bikontinuierlicher Nanokomposite mit Phasentrennung auf der <100‐nm‐Skala.…”
Section: Neue Felder Und Perspektivenunclassified
“…However, application is limited because the structural stability is low and proton conductivity largely decreases upon slight decrease in RH. To solve these problems, POMs have been hybridized with polymers [20][21][22][23][24] especially with those containing amine groups, which serve as protonation sites. While these POM-polymer composites are promising candidates of future solid electrolytes, it is rather difficult to obtain relationship among composition, structure, and property because of the amorphous nature.…”
mentioning
confidence: 99%